Connectivity pattern analysis for virtual simulation design, based on high-performance game analysis - Auccahuasi, Wilver (2021)
In the learning and training processes, simulation is taking a lot of strength due to the ease and recurrence that it allows us, managing to perform it repeatedly until reaching the necessary skills. We find simulation in different applications Such as doctors, in engineering, where what is tried is to reproduce the experimentation environment in a similar way, that is why we find today a number of applications, tools, programming languages, dedicated development environments to be able to implement simulation environments. The present work proposes a method to be able to analyze the connectivity patterns to be able to recommend the use and applications of the different types of networks, making an analysis of these connections in the realization of video games, in the study various video games that we can find were evaluated In the market, these video games have a particularity that within their simulation structure requires a high calculation capacity, so it is recommended so that it can be installed against a good capacity of memory, storage, processor and a powerful graphic processor, who is in charge of the rendering of the scenarios, game analysis and the greater amount of calculation necessary to carry out the game, games such as Valorant, Fornite and League of Legends were evaluated, games that require high computational capacity, added to a good connectivity of network, WIFI connections were evaluated in the 2.4GHz 5GHz bands and by RJ45 connector, the results show that before a constant speed of the same network the 5GHz connection is the connection where the games have a better performance, in second place is the connection by RJ45 or better known as a network cable connection and finally in third place is the WIFI connection to 2.4 GHz, these results can help the design of applications related to virtual simulation independent of the simulation engine.